Effect of photoperiod on follicular IGF-1 and oocyte quality independently of metabolic status in buffalo heifers. Issue 1 (2nd January 2019) - Salzano, Angela; Gasparrini, Bianca; Vecchio, Domenico; Longobardi, Valentina; Baruselli, Pietro Sampaio; Balestrieri, Anna; Licitra, Francesca; D'Occhio, Michael; Neglia, Gianluca
Abstract: The aim of this study was to determine whether buffalo heifers maintained at a constant live weight (LW) and body condition score (BCS) by a restricted diet show changes in reproductive function in response to changes in day length. Heifers were fed a low energy diet (86% daily intake recommended for the species) throughout the study, which involved an 8-week period of decreasing day length and a 7-week period of increasing day length. Weekly, LW, BCS and ovarian follicular/oocyte population were assessed. Blood and follicular fluid samples were taken at the time of ovum pick-up for hormone analyses and at 30-day intervals to measure metabolic substrates. Buffalo heifers maintained LW and BCS throughout the study and blood concentrations of the main metabolic hormones, such as GH, insulin, IGF-1 and thyroid hormones were not influenced by photoperiod. Likewise, there were no differences in metabolic substrates such as glucose, NEFA, triglycerides and HDL cholesterol, suggesting that the metabolic condition remained essentially the same. During increasing day length periods, the number of total follicles (8.4 ± 0.5 vs. 11.9 ± 0.6; p < .01), cumulus-oocyte complexes (2.2 ± 0.3 vs 4.3 ± 0.5; p < .01) and superior quality Grade A + B COCs (0.2 ± 0.1 vs 1.1 ± 0.2; p < .01) decreased. These features were associated to reduced oestradiol levels both in plasma (3.9 ± 0.4 vs 9.2 ± 0.5 pg/mL; p < .01) and follicular fluid (49.7 ± 12.9 vs. 109.1 ± 25.8 ng/mL; p = .05), as well as to reduced intrafollicular IGF-1 levels (45.5 ± 4.0 vs. 58.5 ± 3.9 ng/mL; p < .05). These findings suggest that the ovarian function in buffalo heifers is influenced by photoperiod independent of nutritional and metabolic status. Highlights: Metabolic profile, LW and BCS do not change in buffalo heifers on a restricted diet Photoperiod affects ovarian function in heifers regardless of metabolic status Follicular and oocyte population decrease in increasing day length periods Oestradiol and IGF-1 levels in follicular fluid are affected by photoperiod